2019
DOI: 10.1186/s12939-019-1034-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition among children of migrant construction workers in Ahmedabad, India

Abstract: Background Millions of poor households in India undertake short duration rural to urban migration along with their children to find work in the informal economy in the city. While literature has documented the precarity of such temporary jobs, typically characterized by low wages, insecure jobs, harsh recruitment regimes and economic vulnerability, little is known about its implications for children who migrate with their parents to the city. In this study, we draw attention to children of migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
1
9
1
Order By: Relevance
“…Singh et al [134] indicated that poor access to clean water often leads to child malnutrition, since the consumption of unpurified water can lead to diarrhea and other waterborne infections. This finding is also validated by Ravindranath et al [24].…”
Section: Poor Access To Water and Sanitationsupporting
confidence: 85%
See 1 more Smart Citation
“…Singh et al [134] indicated that poor access to clean water often leads to child malnutrition, since the consumption of unpurified water can lead to diarrhea and other waterborne infections. This finding is also validated by Ravindranath et al [24].…”
Section: Poor Access To Water and Sanitationsupporting
confidence: 85%
“…Therefore, this review paper intends to fill this research gap by assessing the factors that influence the nutritional status of children under five years in South Africa using available literature. The United Nations International Children Emergency Funds' theoretical framework of causes of child malnutrition groups factors that cause child malnutrition into three groups, which are basic, underlying, and immediate causes [24]. The UNICEF theoretical framework of causes of child malnutrition can act as a catalyst in achieving the objective of this review, by providing guidelines on the existing theory about the causes of child malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…McKay et al (51) argue that migrants' health issues and their context are distinct from those of other marginalised communities and the effect of migration itself on their health is complex and varies across migrant groups. Studies have shown that migrant workers in India face multiple challenges like occupational hazards because of unsafe work conditions (52), higher prevalence of chronic diseases compared to those with no history of migration (53) and insufficient nutritional intake (54), subjects that continue to be ignored by the media. The media's narrow focus on infectious diseases outbreaks, preventive care and sanitation issues while covering migration and health could also be because almost all the stories linked to health were filed from the destination states/cities, and newspapers tend to give salience to those aspects of stories that were deemed of interest to their readers (55).…”
Section: Discussionmentioning
confidence: 99%
“…In India, 19.8 million children below the age of 6 years are malnourished, where one in every three children suffer from malnutrition [20]. A case study of Migrant workers' children in Ahmedabad, India revealed that out of 131 children, 52 children were stunted, 29 were wasted, and 66 were underweight due to malnutrition [21]. The prevalence of undernutrition leads to deterioration in physical and cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%